Optimal midcourse guidance law for the exo-atmospheric interceptor with solid-propellant booster - Zhao, Shilei; Chen, Wanchun; Yang, Liang; Wang, Minghao (Aerospace science and technology, 2022)
This paper focuses on the midcourse guidance law for the exo-atmospheric interceptor with solid-propellant booster to intercept a target in the Keplerian orbit, in which the thrust direction command is provided under the typical framework of predictor-corrector algorithm. Firstly, an analytical solution is derived to predict the burnout velocity and position vectors, in which the thrust vector is assumed to be along the velocity vector. Secondly, the predicted values are used to formulate a set of nonlinear algebraic equations to determine the desired burnout velocity direction to impact the target. Actually, those equations are transcendental because Lambert's problem with unspecified time-of-flight is involved. Then, Newton-Raphson method is used to solve the problem. In the calculation process, the Jacobian matrix corresponding to the equations is derived in an analytical manner, which significantly improves the computational efficiency. Thirdly, an optimal correction guidance law is constructed to steer the interceptor to achieve the desired burnout velocity direction. Finally, convergence evaluation, optimality verification, and Monte Carlo simulations are carried out to test the performance of the proposed guidance law. The results show that it not only performs well in providing the optimal guidance command, but also has high computational efficiency and guidance accuracy. Moreover, it has great robustness even in large dispersions and uncertainties.